(untitled) (Brazilian Journal of Health Research, 2023)
Sarcoidosis is a chronic and multisystemic granulomatous disease with unknown etiology. The skin is affected between 9 and 37% of cases. The histopathology is characterized by the presence of non-caseating granulomas, with little or no amount of surrounding lymphocytes. Clinically, papules and plaques are the lesions most observed, but a wide morphological variability of skin lesions is described, such as psoriasiform, ichthyosiform, atrophic and ulcerative. We reported a case of systemic sarcoidosis with skin involvement in four locations and distinct clinical manifestations in each of them.